A Method of Estimating Equatorial Plasma Vertical Drift Velocity and Its Evaluation Using C/NOFS Observations. Issue 7 (19th July 2019) - Marew, H.; Nigussie, M.; Hui, D.; Damitie, B.
Abstract: To understand the dynamics of the equatorial ionosphere and mitigate its effect on radio wave propagation, vertical ion drift velocity empirical models have been developed using limited ground‐based and/or space‐based observations. These models, however, have not yet been validated in detail using recent observations for sufficiently different longitudinal sectors. In this paper we have evaluated the performance of two empirical models and also propose a simplified vertical drift velocity model based on basic physics laws (i.e., Ampere's and Ohm's laws) that we call it parameterized drift velocity (PDV) model. These models have been applied to estimate the E region electric field and the associated F regionE ×B drift velocity using observed horizontal magnetic fields, due to equatorial electrojet current, as model driver input. Drift velocities obtained from these models are compared with the Communication/Navigation Outage Forecasting System (C/NOFS) satellite in situ vertical drift observations for different longitudinal sectors. It is found, for all longitudinal sectors considered in this study, that the vertical drift velocity obtained from a model based on physics laws has shown better agreement with C/NOFS observations as compared to the outputs of other empirical models. Moreover, it is shown that the Anderson empirical model performs better than the International Reference Ionosphere model. Key Points: Ionospheric E layer zonal electric field can be estimated using Ohm's law, conductivity model, and equatorial magnetometers observations A simplified vertical drift velocity model based on Ampere's and Ohm's laws is developed The performance of the new technique is better than IRI2016 and Anderson models in describing the C/NOFS vertical drift velocity observation